2008
DOI: 10.1111/j.1399-6576.2007.01529.x
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological risk of anaesthetic breathing circuits after extended use

Abstract: The extended use of breathing circuits for 48 and 72 h does not increase significantly the risk of contamination, provided that HME filters are changed separately for every patient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
13
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 17 publications
4
13
0
3
Order By: Relevance
“…Our microbiological results were obtained in ABC applied for low-flow anaesthesia; samples obtained from the y-piece and the water trap indicated no difference in the rate of endoluminal contamination of ABC after 1 day compared to 7 days of use. This agrees with the findings of smaller investigations in the past 30,31 and another recent study, 18 which also revealed no increase in bacterial contamination on the inner surface after use of the circuits for more than 24 h. The rate of endoluminal bacterial contamination (7.8% and 5.9% after day 1 and 7 respectively) in our study was within the range reported by colleagues from Germany (3.33% and 5.56% after day 1 and 3 respectively) 3031 and Australia (54% and 46% after day 1 and 7 respectively). 18 Interestingly, the bacterial species found in our study in the ABC on day 1 and day 7 differed markedly.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our microbiological results were obtained in ABC applied for low-flow anaesthesia; samples obtained from the y-piece and the water trap indicated no difference in the rate of endoluminal contamination of ABC after 1 day compared to 7 days of use. This agrees with the findings of smaller investigations in the past 30,31 and another recent study, 18 which also revealed no increase in bacterial contamination on the inner surface after use of the circuits for more than 24 h. The rate of endoluminal bacterial contamination (7.8% and 5.9% after day 1 and 7 respectively) in our study was within the range reported by colleagues from Germany (3.33% and 5.56% after day 1 and 3 respectively) 3031 and Australia (54% and 46% after day 1 and 7 respectively). 18 Interestingly, the bacterial species found in our study in the ABC on day 1 and day 7 differed markedly.…”
Section: Discussionsupporting
confidence: 93%
“…Particularly during low-flow anaesthesia, when increased temperature and humidity within the circle system occurs, the risk of endoluminal bacterial growth during prolonged use of ABC has to be considered, as the CO2-absorber might provide a very hostile environment for microorganisms. Of the three studies mentioned above, 18,19,30 only one provided data on contamination rates of the outer surface of ABC; 19 these were 12% and 21% after 1 and 7 days of use respectively, and thus lie in the same range as our findings (7% vs. 17%). Our microbiological results were obtained in ABC applied for low-flow anaesthesia; samples obtained from the y-piece and the water trap indicated no difference in the rate of endoluminal contamination of ABC after 1 day compared to 7 days of use.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Although in general the ABMs’ internal BCSs are regarded to be free of micro-organisms [5], [6], [7], [8], [9], we could demonstrate the presence of bacterial contamination. Our findings raise old questions concerning the origin of the bacteria, the potential risk they may harbour in terms of cross-contamination within patients, and the consequences for infection control.…”
Section: Discussionmentioning
confidence: 97%
“…A number of studies explored bacterial contamination of ABMs concentrating on disposable breathing-circuit-systems (BCS), yet, focusing on the inspiratory and expiratory port of the ABMs or the machine’s absorber as reported [5], [6], [7], [8], [9]. These studies did not observe clinically relevant contamination at the investigated locations, nor could they provide evidence of an association between patient’s pharyngeal micro-flora and the bacteria retrieved from the ABM.…”
Section: Introductionmentioning
confidence: 99%